Integrating Virtual Laboratories and Trainer Kits for Computer Network Engineering Practicum Learning in a Vocational School - Kamal; Muhammad Yaumi; M.Yusuf T; Abdul Syatar (Information Technology Education Journal, 2026)
Purpose – This study examined the implementation of a hybrid practicum model integrating Trainer Kits and Virtual Laboratories in computer network engineering learning at SMK Telkom Makassar, Indonesia. The study aimed to analyze changes in students’ learning outcomes and examine students’ perceptions of the integrated learning media. Design – A quasi-experimental one-group pretest–posttest design was employed involving 36 vocational students. The intervention was conducted through hybrid practicum sessions in which students performed virtual simulations before implementing configurations using the physical Trainer Kits. Data were collected using cognitive achievement tests and a student perception questionnaire and analyzed using descriptive statistics, normalized gain analysis, and paired-sample t-test. Findings – The results showed a notable improvement in learning outcomes, with the mean score increasing from 54.38 in the pretest to 86.25 in the posttest, resulting in an N-Gain of 0.698, indicating a moderate to high level of learning improvement. Students’ perceptions were also highly positive, with an overall acceptance score of 91.6%. Research implications – However, because the study employed a one-group pretest–posttest design without a control group, the findings should be interpreted as preliminary evidence of improvement following the implementation of the hybrid practicum model. Originality – This study examined the implementation of a hybrid practicum model integrating Trainer Kits and Virtual Laboratories in computer network engineering learning and provides evidence of its potential to improve learning outcomes and student perceptions in vocational education contexts.